Optical Coherence Tomography in Multiple Sclerosis Clinical Applications - Petzold, Axel (Springer International Publishing : Imprint: Springer, 2016)
This book gives a clinical context to optical coherence tomography (OCT) findings, while considering the differential diagnosis and providing patient management guidance.  Relevant anatomical and technical aspects are discussed, followed by a pragmatic illustration of the use of OCT for the clinical spectrum of multiple sclerosis and optic neuritis, and finishing with information on monitoring ocular side effects of recently approved disease-modifying treatments in multiple sclerosis.  Optical Coherence Tomography in Multiple Sclerosis: Clinical Applications is aimed at clinical neurologists working with patients suffering from MS and general neurologists who see patients with visual symptoms in their daily practice. Ophthalmologists sharing clinical responsibilities with neurologists for patients under disease-modifying treatments will also find the book of interest.